Laser-heated needle for biopsy tract ablation: In vivo study of rabbit liver biopsy. (February 2021) - Raziff, Hani Hareiza Abd; Tan, Daryl; Tan, Soon Hao; Wong, Yin How; Lim, Kok Sing; Yeong, Chai Hong; Sulaiman, Norshazriman; Abdullah, Basri Johan Jeet; Wali, Haryanti Azura Mohamad; Zailan, Nur Azmina Mohd; Ahmad, Harith
Highlights: A laser-heated core biopsy needle system was developed. The system was tested in-vivo using New Zealand White rabbit's liver model. The system was able to reduce hemorrhage in the liver for up to 93.8%. HPE results showed that coagulative necrosis was achieved along the biopsy tract. Abstract: Purpose: To investigate the efficacy of a newly-developed laser-heated core biopsy needle in the thermal ablation of biopsy tract to reduce hemorrhage after biopsy using in vivo rabbit's liver model. Materials and methods: Five male New Zealand White rabbits weighed between 1.5 and 4.0 kg were anesthetized and their livers were exposed. 18 liver biopsies were performed under control group (without tract ablation, n = 9) and study group (with tract ablation, n = 9) settings. The needle insertion depth (~3 cm) and rate of retraction (~3 mm/s) were fixed in all the experiments. For tract ablation, three different needle temperatures (100, 120 and 150 °C) were compared. The blood loss at each biopsy site was measured by weighing the gauze pads before and after blood absorption. The rabbits were euthanized immediately and the liver specimens were stained with hematoxylin-eosin (H&E) for further histopathological examination (HPE). Results: The average blood loss in the study group was reduced significantly (p < 0.05) compared to the control group. The highest percentage of bleeding reduction was observed at the needle temperature of 150 °C (93.8%), followed by 120 °C (85.8%) and 100 °C (84.2%). The HPE results show that the laser-heated core biopsy needle was able to cause lateral coagulative necrosis up to 14 mm diameter along the ablation tract. Conclusion: The laser-heated core biopsy needle reduced hemorrhage up to 93.8% and induced homogenous coagulative necrosis along the ablation tract in the rabbits' livers. This could potentially reduce the risk of tumor seeding in clinical settings.